Depression at Workplaces: The Factors that Influencing and How to Overcome the Issues - Binti Ismail, Fadillah; Owaida, Nesreen Ibrahim (Journal of Techno-Social, 2023)
Depression is a complex condition with a wide range of expressions of opinions, feelings, and attitudes that can directly strike anyone, and when we consider someone suffering from workplace depression, an amount of work and non-work-related aspects might be at work. Although depression is treatable, it is frequently a lifelong condition with periods of wellness punctuated with depressed illnesses. The objective of the study is to discuss the factors that influencing depression among workers and how to overcome these issues to improve their productivity. To emphasize, this study discussed a various common risks factor that led to depression at workplace in the first subtopic. In the discussion stated about toxic workplace environment, workplace sexual harassment, discrimination, abusive and bullying and excessive workload. Meanwhile employer is a main role to establishing supportive work environment to improve workers motivation at a workplace. In second subtopic discussed the several awareness that can be implemented by three categories which is employer, the authorities and by individuals to play their own role to overcome the depression issue such as providing programme that can increasing self-awareness among community. People may require a more comprehensive understanding of depression, as well as the significance of the work environment in impacting job incapacity due to depression. Thus, this paper will provide a better understanding about the issues for future direction.